Preparation of Vocational College Graduates as Skilled Workforce in the Local Construction Industry - Manap, Norpadzlihatun; Hassan, Noor Sakinah; Syahrom, & Noor Shahifah (Journal of Technical Education and Training, 2017)
Construction industry is growing rapidly along with the development of a country. This situation caused a high demand of workforce in this industry until the hiring of foreign workers becomes a necessity, as seen in Malaysia’s scenario. To overcome this issue, the government of Malaysia established many Technical and Vocational Education and Training (TVET) institutes that have potential to produce local workforce as highly skilled workers in construction industry. However, the preparation of these institutes for their students have never been analyzed, as the involvement of students from TVET institutes in local construction industry as skilled workers is still low, making their preparation method as an issue. Therefore, this research will identify the types of preparation method by TVET institutes for students pursuing programmes related to construction industry, and to assess teaching strategies for programmes related to construction industry to improve student preparation to become skilled workforce. To achieve the main objectives of this research, data collection is performed by interviewing teachers from three Vocational Colleges (VC) namely VC Kluang, VC Klang and VC Taiping, which are teaching Construction Technology programmes. It can be concluded that VCs have adequate preparation to produce graduates that can become skilled workforce in the construction industry. The results conclude that there are two types of preparation method made by the VCs; preparation method in the classroom and preparation method outside the classroom. The classroom preparation method includes laboratory training and teaching using modules designed to fit industrial needs. The results from outside classroom preparation include extra-curricular activities and construction site visits. As for results of the second objective, the teaching strategies to improve student preparation for skilled workforce is through the emphasis of safety during construction to students and the raising of student interest in Construction Technology programmes through industry participation. However, actions need to be taken in order to solve the issues that include a lack of equipment and no large area for computers. This study can help VCs to enhance the student preparedness to work in the construction industry.